Intervention Development for People with Muscle Dysmorphia Symptoms: Best Practice and Future Recommendations. Issue 4 (19th May 2023) - Sandgren, Sebastian S.; Lavallee, David
Abstract: Symptoms of muscle dysmorphia carry significant risks for people's health and wellbeing. A key priority is therefore to support this group in reducing their symptoms and distorted behaviors to mitigate against the development of clinically severe muscle dysmorphia. However, few interventions exist and there is a need to develop new programs urgently. In this article, we provide researchers and practitioners with evidence-based recommendations on how to effectively achieve this. Recommendations are based on the health intervention development literature and the Intervention Mapping Protocol is introduced as a valuable tool for systemizing the development process. We encourage and now call on researchers and practitioners to action this imminent and important task of developing interventions to address muscle dysmorphia symptoms.